Design and implementation of secured e-commerce digital learning for the educational system in Nigeria - Sulaimon, Hakeem Adewale; Owamoyo, Najeem (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
In this modern era, learners struggle with mastering or understanding whatever concepts they are taught in their education. This might be because of ineffective teaching strategies or a lack of passion on the side of the teachers. Therefore, this study develops a Secured E-commerce Digital Learning (SEDL) website application using the Django framework of Python and the system provides room for an administrator to list products for sale, accept payments, and complete students' orders. The developed SEDL website will be a helpful teaching tool for the fundamentals of e-commerce. The study also examined the steps required to design an online ordering and security architecture in the application. Data safety, privacy, and user trust are the major challenges. The SEDL application is implemented to encrypt all data transmitted over the client-server communication channel using the Secured Electronic Transaction (SET) protocol and Advance Encryption Standard (AES) cryptographic. The study then makes some recommendations, one of which is that the government should provide effective regulations that would facilitate the implementation of secured e-commerce digital learning for future growth in the Nigerian higher education system.